(untitled) (Journal of Interior Design and Academy, 2024)
Living spaces change and develop depending on many factors such as the requirements of the age, people’s wishes and needs, traditions, environmental- regional factors, climate changes, natural disasters. Depending on these factors, mobile houses and water related housese are housing types that are sensitive to the environment and support sustainable living. The aim of this study is to provide information on the functions, environmental relations and interior features of waterrelated housing. Two samples with strong and distinct environmental-interior relations were selected for further investigation. Document analysis was used as the research method. As a result of the study, the adaptation, sensitivity and energy efficiency of water-related houses with their environment come to the fore in their designs. In addition, these environmentally friendly buildings are sustainable thanks to the natural energy they produce from natural resources. It was concluded that the preference of water-related houses has positive contributions for both human health and the environment.